Pengaruh Kualitas Audit, Debt Default, dan Opinion Shopping terhadap Penerimaan Opini Audit Going Concern - Pratiwi, Aprilia Lenny; Srimindarti, Ceacilia (Gorontalo Accounting Journal, 2025)
This study aim to analyze the effect of audit quality, debt default, and opinion shooping on the issuance on going concern audit opinion in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The sample was selected using purposive sampling, resulting in 78 companies. Data were collected through documentation and analyzed using logistic regression withe SPSS version 27. This study demonstrates that going concern audit opinion is significantly impacted by audit quality, debt default, and opinion selection acceptance. In conclusion, The going concern audit opinion is significantly impacted by these three factors. Good audit quality reduces the possibility of obtaining an opinion on a going concern, while debt default and opinion selection raise the possibility of getting that opinion.